Children affected by HIV/AIDS attending programmes to improve psychosocial well-being: current status and pathways to effective interventions - Skeen, Sarah Ann (Department of Psychiatry and Mental Health, 2018)
The HIV/AIDS pandemic has a substantial impact on children across the globe and particularly in sub-Saharan Africa. Across sub-Saharan Africa, there are a number of organisations and programmes providing care and support to children affected by HIV/AIDS. However, this strong programmatic focus on mitigating the impact of HIV/AIDS on children at community level has not been matched with concomitant research investment into the needs of children who attend these programmes at these organisations, their health and development, how these organisations work, and whether they are effective. This thesis attempts to address this gap by reporting on three separate analyses of data from the Child Community Care study in South Africa and Malawi, and a systematic review on interventions to improve psychosocial wellbeing of this group. The first analysis describes developmental outcomes of children affected by HIV/AIDS attending community-based programmes and the types of services these children are receiving. The second analysis reports on the mental health of carers of children affected by HIV. In the third analysis I report on the relationship between different forms of violence and mental health status among children affected by HIV/AIDS in the sample. The fourth part is a systematic review of interventions developed to improve the psychosocial well-being of children affected by HIV/AIDS, published between January 2008 and February 2016. The results of these studies highlight the complex needs of children affected by HIV/AIDS attending these organisations. CBOs are reaching a vulnerable group of children and their families, and are well-placed to intervene with this population. There are promising models of interventions available, although the evidence base remains small. Caregivers should not be neglected in programming; parenting programmes provide a potential mechanism for delivering integrated interventions that address multiple risk factors for caregiver and child wellbeing. Mental health, particularly of caregivers, should be explicitly addressed as a part of CBO programming. However, funding for programming needs to be implemented with opportunities for training and supervision. In addition, there is a need for increased partnerships between practitioners and researchers in order to evaluate existing programmes and to design evaluation studies that suit community settings, and that can feed into the growing evidence base.